2023
DOI: 10.2196/preprints.45839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feasibility, perceived impact, and acceptability of a socially assistive robot to support emotion regulation with highly anxious university students (Preprint)

Abstract: BACKGROUND Mental health difficulties among university students have been rising rapidly over the last decade, and the demand for university mental health services commonly far exceeds available resources. Digital interventions are seen as one potential solution to these challenges. However, as in other mental health contexts, digital programmes often face low engagement and uptake; and the field lacks usable, engaging, evidence-supported mental health interventions that may be used fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Purrble was originally developed for children in moments of situated distress, but it has since been well-accepted across child and student populations delivering notable benefits for ER. [47][48][49][50] Among a small sample of 21 LGBTQ+ young people, Purrble was found to be a feasible and acceptable intervention with continued device engagement across a 2-week deployment. 47 Notably, access to Purrble was also associated with a reduction in anxiety symptoms and self-harmful thoughts.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 98%
See 4 more Smart Citations
“…Purrble was originally developed for children in moments of situated distress, but it has since been well-accepted across child and student populations delivering notable benefits for ER. [47][48][49][50] Among a small sample of 21 LGBTQ+ young people, Purrble was found to be a feasible and acceptable intervention with continued device engagement across a 2-week deployment. 47 Notably, access to Purrble was also associated with a reduction in anxiety symptoms and self-harmful thoughts.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 98%
“…[47][48][49][50] Among a small sample of 21 LGBTQ+ young people, Purrble was found to be a feasible and acceptable intervention with continued device engagement across a 2-week deployment. 47 Notably, access to Purrble was also associated with a reduction in anxiety symptoms and self-harmful thoughts. Qualitative data indicated that this was linked to Purrble supporting ER practices (eg, grounding, soothing) to prevent young people acting on their self-harmful urges and, in some cases, preventing them from considering self-harm at all.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 98%
See 3 more Smart Citations